Freelisting as a suitable method to estimate the composition and harvest rates of hunted species in tropical forests - Oliveira, Marcela Alvares; El Bizri , Hani Rocha; Morcatty, Thais Queiroz; Messias, Mariluce Rezende; Doria, Carolina Rodrigues da Costa (Ethnobiology and Conservation, 2022)
The aim of this study was to test the use of measures obtained from freelisting as possible surrogates of the harvest rate of game species. For this purpose, we interviewed 100 rural and urban hunters in southwestern Amazonia to obtain the frequency of citations of each hunted species through freelisting and gather information on the number of individuals hunted per species in the last five hunting events through hunting recalls. We assessed the relationship between the percentage of records per species by each method through a generalized linear model, and then compared the predicted values obtained from this model with the values observed in our dataset using Pearson’s correlation. During freelisting, forty-three taxa were listed in 608 citations as hunted by the informants. Freelisting provided data on around twice the number of species obtained from recalls. During the last five hunting trips, urban hunters reported the hunting of 164 individuals of 18 species, representing 54.5% of the freelisted species. Rural hunters caught 146 individuals of 21 species, 60.0% of the freelisted species. We found a strong logistic relationship between the harvest rates, i.e., percentage of individuals hunted per species from recalls, and the freelisting percentage citations of game species, with the estimated and observed values of harvest rates highly matching (Pearson’s R = 0.98, p < 0.0001). The freelisting method allowed a good estimate of the composition and the harvest rates of hunted species. The formula produced in this study can be used as a reference for further studies, enabling researchers to use freelisting effectively to assess the composition of hunted species and to address the difficulty of obtaining reliable data on species harvest rates in tropical forests, especially in short-term studies and contexts in which hunters distrust research.